Altered Developmental Expression of the Astrocyte-Secreted Factors Hevin and SPARC in the Fragile X Mouse Model - Wallingford, Jessica; Scott, Angela L.; Rodrigues, Kelly; Doering, Laurie C. (Frontiers in Molecular Neuroscience, 2017)
Astrocyte dysfunction has been indicated in many neurodevelopmental disorders, including Fragile X Syndrome (FXS). FXS is caused by a deficiency in fragile X mental retardation protein (FMRP). FMRP regulates the translation of numerous mRNAs and its loss disturbs the composition of proteins important for dendritic spine and synapse development. Here, we investigated whether the astrocyte-derived factors hevin and SPARC, known to regulate excitatory synapse development, have altered expression in FXS. Specifically, we analyzed the expression of these factors in wild-type (WT) mice and in Fmr1 knock-out (KO) mice that lack FMRP expression. Samples were collected from the developing cortex and hippocampus (regions of dendritic spine abnormalities in FXS) of Fmr1 KO and WT pups. Hevin and SPARC showed altered expression patterns in Fmr1 KO mice compared to WT, in a brain-region specific manner. In cortical tissue, we found a transient increase in the level of hevin in postnatal day (P)14 Fmr1 KO mice, compared to WT. Additionally, there were modest decreases in Fmr1 KO cortical levels of SPARC at P7 and P14. In the hippocampus, hevin expression was much lower in P7 Fmr1 KO mice than in WT. At P14, hippocampal hevin levels were similar between genotypes, and by P21 Fmr1 KO hevin expression surpassed WT levels. These findings imply aberrant astrocyte signalling in FXS and suggest that the altered expression of hevin and SPARC contributes to abnormal synaptic development in FXS.